Euphemisms in Toba Batak Speech Actions with Pakpak Language: Pragmatic Studies - Purba, Patramaja (L'Geneus : The Journal Language Generations of Intellectual Society, 2020)
The problem in this research is what are the forms of euphemisms and speech acts that have euphemisms. The purpose of this study is to determine the forms of euphemisms, the meaning of euphemisms in the speech acts of the Toba Batak language with the Pakpak language. The benefits of this research are to contribute theoretically to various forms of euphemisms, and add insight and foster pride for the Batak community. The research method used in this research is descriptive, with sources. The data were collected using the following techniques: observation, interview and document study. Based on the theory used in this research, namely Searly's theory. Data analysis found euphemisms in the Toba Batak language speech acts with Pakpak language which can be seen from representative speech acts, directive speech acts, commissive speech acts, expressive speech acts, and declarative speech acts. The form of euphemisms is in the form of words, phrases and clauses. The euphemisms of the Toba Batak language with the Pakpak language found in this study are the speech acts of locus, illocution and perlocution. The use of euphemisms in speech acts in every Toba Batak language and Pakpak language has the function of smoothing speech to appreciate, respect and keep off language that is not pleasant. The results showed that: The Batak Toba people with Pakpak still have euphemistic or subtle language in every conversation in a certain context.